Legal Protection for Women as Victims of Rape in the Perspective of Feminist Legal Theory - Santoso, Niken Larasayu; Suhariyanto, Didik; Setiawan, Puguh Aji Hari (Media Hukum Indonesia (MHI), 2025)
Sexual violence against women, particularly rape, remains a serious issue in Indonesia despite the enactment of Law Number 12 of 2022 on Sexual Violence Crimes (UU TPKS). However, in practice, there is a significant gap between normative ideals and the reality of law enforcement. Many law enforcement officers are reluctant or have yet to fully understand the UU TPKS, resulting in sexual violence cases still being processed under the KUHP. Consequently, victims experience revictimization, limited access to restitution and recovery services, and a legal system that fails to recognize women’s experiences as complete legal subjects. This study employs a normative legal method with a qualitative approach. The primary sources of data consist of secondary legal materials, including legislation (particularly UU TPKS and the KUHP), court decisions (West Jakarta District Court Decisions Number 412/Pid.B/2023 and 722/Pid.B/2023), scholarly journals, and literature related to Feminist Legal Theory. The analytical technique used is sociological interpretation to connect legal norms with social realities, examined through the framework of Feminist Legal Theory (FLT) as a critical tool to identify gender bias within the legal system. The findings reveal that legal protection for women who are victims of rape has not yet fully aligned with the principles of substantive justice and feminist perspectives. Although the UU TPKS offers a victim-centered approach and recognizes various forms of non-physical violence, its implementation remains hindered by patriarchal legal culture, insufficient training for law enforcement officers, and weak inter-institutional coordination. Court decisions applying the UU TPKS tend to be more responsive to victims’ trauma compared with those applying the KUHP.